SELF MANAGEMENT EDUCATION (DSME) SEBAGAI METODE ALTERNATIF DALAM PERAWATAN MANDIRI PASIEN DIABETES MELITUS DI DALAM KELUARGA. - Sutandi, Aan (MAJALAH ILMIAH WIDYA, 2012)
Living and coping with diabetes can be difficult. However, it can have a full and active life even though for those who havediabetes. Diabetes self-management education (DSME) is the ongoing process of facilitating the knowledge, skill, and ability necessaryfor diabetes self-care The objective of this article is to discuss how to manage diabetes may not be easy but the benefits are worththe effort. The method used library research and analyzed descriptively. The conclusion are: (1) Diabetes self-management educationgives the patiend and family the skills and confidence they need to learn to manage the diabetes. (2) The overall objectives of DSMEare to support informed decision-making, self-care behaviors, problem-solving and active collaboration with the health care team andto improve clinical outcomes, health status, and quality of life.